A Sensitive Method for Determination of Carbendazim Residue in Vegetable Samples using HPLC-UV and Its Application in Health Risk Assessment - Buran Phansawan (Science Faculty of Chiang Mai University, 2019)
Carbendazim is a fungicide widely used in vegetable growing and its residue was often detected. We developed a sensitive method using high performance liquid chromatography-UV detection (HPLC-UV) for determining carbendazim residue in vegetables and assessed the health risk from contaminated vegetable consumption. The consumption data was collected from 244 participants aged 35-65 years living in Suthep subdistrict of Chaing Mai city while vegetable samples were collected from Chiang Mai city fresh markets during August to October 2011. The developed method provided good recoveries of carbendazim from spiked pooled vegetable samples ranged from 92.5 % to 96.0 % with the relative standard deviation (RSD) of 2.1 % to 5.9 % at spiked levels of 0.05-0.30 mg kg-1. The limit of detection (LOD: 0.003 mg kg-1) as well as the limit of quantitation (LOQ: 0.030 mg kg-1) of the developed method is sensitive to detect carbendazim residue in vegetables far below the Codex Maximum Residue Limits (MRLs) such as 0.05 mg kg-1 set for cucumber. The health risk assessment of carbendazim from consumption of 5 common kinds of vegetables, i.e. tomato, cucumber, kale, cauliflower, and ginger, was performed by comparing calculated daily intake (CDI) with acceptable daily intake (ADI). It was found that the CDI of carbendazim residue from consumption of tomato (64.1 %), cucumber (59.6 %), and kale (56.7 %) were greater than 50 % of ADI while of cauliflower (19.3 %), and ginger (0.9 %) were much lower. The present results showed that consumption of some contaminated vegetables may pose the health risk though the commination may vary from season to season. Furthermore, the developed method could be used to survey carbendazim residue in vegetables as well as fruits by using HPLC-UV which is a common apparatus available in toxicology laboratory.